Smart Parking System Based on Internet of Things Technology for Realtime Parking Slot Monitoring - Yera Nafisy; Satria Gunawan Zain; Kurnia Prima Putra (Journal of Embedded Systems, Security and Intelligent Systems, 2025)
This study aims to develop a parking system based on Internet of Things (IoT) technology to address the issues of parking space limitations and efficiency. The system is designed using an HC-SR04 sensor and an ESP32 microcontroller, with data displayed in real-time through an Android application based on MIT App Inventor. The research employed applied research methods, with data collection techniques involving observation and questionnaires. Data analysis was conducted using descriptive quantitative methods. The results showed that the system has a functionality value of 1 or 100%, and a usability level of 81%–100%, indicating that the system is highly suitable for use. Additionally, this system is energy-efficient, with a power consumption of only 0.9105 watts (5.607 mWh for 6 hours of use), and the Wi-Fi connection remains stable up to a distance of 20 meters. Sensor testing revealed that at distances of 50–100 cm, objects can still be detected up to an angle of ±45°, while at a distance of 150 cm, effective detection only occurs within the angle range of -30° to 30°. At a distance of 200 cm, objects are not detected at an oblique angle. These results demonstrate that an IoT-based smart parking system can function effectively and efficiently if the sensor placement is adjusted to its optimal range.